2012
DOI: 10.1007/s12011-012-9558-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pigment Epithelium-Derived Factor (PEDF) in Arsenic-Induced Cell Apoptosis of Liver and Brain in a Rat Model

Abstract: Although studies have shown that arsenic exposure can induce apoptosis in a variety of cells, the exact molecular mechanism of chronic arsenicosis remains unclear. Based on our previous study on human serum, the present study was to determine whether pigment epithelium-derived factor (PEDF) plays a role in the damage induced by chronic arsenic exposure in a rat model and to explore the possible signaling pathway involved. Thirty male Wistar rats were randomly divided into three groups and the arsenite doses ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Because Bcl-2 homodimerizes with itself and forms heterodimers with Bax and Bax is functionally neutralized by heterodimerization with Bcl-2, the ratio of Bcl/Bax protein could ultimately tip the balance toward cell survival or cell death 38) . Zhang et al (2013b) reported that the ratio of Bax/Bcl-2 in the liver and brain following exposure to As was significantly increased compared with that of their control group 18) . In the present study, subchronic exposure to As also increased the ratio of Bax/Bcl-2 expression in the hippocampus of mice, which is consistent with the results reported by Zhang et al (2013b) 18) .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Because Bcl-2 homodimerizes with itself and forms heterodimers with Bax and Bax is functionally neutralized by heterodimerization with Bcl-2, the ratio of Bcl/Bax protein could ultimately tip the balance toward cell survival or cell death 38) . Zhang et al (2013b) reported that the ratio of Bax/Bcl-2 in the liver and brain following exposure to As was significantly increased compared with that of their control group 18) . In the present study, subchronic exposure to As also increased the ratio of Bax/Bcl-2 expression in the hippocampus of mice, which is consistent with the results reported by Zhang et al (2013b) 18) .…”
mentioning
confidence: 99%
“…Zhang et al (2013b) reported that the ratio of Bax/Bcl-2 in the liver and brain following exposure to As was significantly increased compared with that of their control group 18) . In the present study, subchronic exposure to As also increased the ratio of Bax/Bcl-2 expression in the hippocampus of mice, which is consistent with the results reported by Zhang et al (2013b) 18) . This indicates that subchronic exposure to As disturbed expression of the Bcl-2 family proteins in the hippocampus of mice.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…NaAsO 2 was administered in drinking water at concentrations of 0, 5, 10, and 50 mg/L. The dose of NaAsO 2 was determined on the basis of LD 50 values in the rats [21]. During the whole experimental period, animals had free access to food and water.…”
Section: Animals and Treatmentmentioning
confidence: 99%